Fatigue analysis of similar and dissimilar solid rod welding using friction welding process - Abdul Mutholib, Osman (2013)
These papers investigate the fatigue analysis of aluminum 1100 and mild steel, similar joining and dissimilar joining using friction welding process. The objective of this research was to determine the joining strength and hardness as the mechanical properties and macrostructure and microstructure of welding area as the weld quality. The parameter for this research is the welding process been weld by using different rotational speed for both similar and dissimilar welding group. For the mechanical properties, fatigue test was conducted to analyze the strength and Vickers hardness test to determine the hardness at the weld joint area. As for the weld quality, optical microscope and measurement microscope was used to analyze the macrostructure and microstructure analysis. The result show that, for the similar welding, the mechanical properties, the fatigue test of similar welding and materials show, 1900 rpm for both materials recorded the longer life cycle. The highest Vickers hardness for both aluminum 1100 and mild steel similar welding are 68.31HV and 257.9HV, respectively. For the dissimilar welding, the mechanical properties showed that 1700 rpm have longer life cycle for fatigue test and have high hardness (209.7 HV) at the welding area. As conclusion, for the similar welding, both materials show the rotational speed at 1900 rpm produce high strength of joining compared to the other groups and for the weld quality, the result show better weld quality compare to other. For the dissimilar welding, the rotational speeds 1700 rpm produce the high strength of joining compared to the other groups and for the weld quality, result show better weld quality compared to other.